Pertumbuhan dan Produksi Tanaman Sawi (Brassica juncea L.) Akibat Pemberian Pupuk Organik dan Anorganik - Rosana M. T. Tulaseket; Linda Ernawati Lindongi; Liz Yanti Andriyani; Fenny S. J. Asyerem (Fakultas Pertanian Universitas Papua, 2023)
This study aimed to determine the effect of applying several organic fertilizers (Papua Nutrient liquid fertilizer, Green Tonik liquid organic fertilizer, Nasa liquid organic fertilizer, Agrica liquid organic fertilizer) and inorganic fertilizers (CPN, NPK 16 : 16 : 16 fertilizer, Solution liquid fertilizer, Urea + KCl + TSP, SP 36) on the growth and production of mustard greens. The design used in this study was a randomized block design (RBD) with 10 treatments which were repeated 3 times. The research treatments were S0: Without Treatment, S1: Papua Nutrient (10 ml/liter of water), S2: POC Green Tonic (3 ml/liter of water), S3: POC Nasa (2 ml/liter of water), S4: POC Agrica ( 5 ml/ liter of water), S5 : CPN fertilizer (5 gram/ plant), S6 : NPK 16 : 16 : 16 (5 gram/ plant), S7 : Liquid chemical fertilizer solution (4 ml/ liter of water), S8 : Urea + KCL + TSP (5 grams/plant) and S9 : SP – 36 (5 grams/plant). Data were analyzed using variance. If the treatment has a significant effect, then the analysis is continued using the Least Significant Difference Test (LSD) with a 95% confidence level. The results showed that the application of several organic fertilizers and inorganic fertilizers showed a significant effect on plant height 3 WAP, number of leaves 3 WAP, number of leaves 4 WAP and plant fresh weight per plot, and had a very significant effect on plant height 4 WAP, leaf width and plant fresh weight per plant. The fertilizer treatment that showed the best results on average was NPK 16: 16: 16 (S) and Urea + KCl + TSP (S8) fertilizers, while the fertilizer treatment that showed the lowest results was Papua Nutrient fertilizer (S1).